Tracking the evolution of sex chromosome systems in Melanoplinae grasshoppers through chromosomal mapping of repetitive DNA sequences - Palacios-Gimenez, Octavio M. [UNESP]; Castillo, Elio R.; Martí, Dardo A.; Cabral-De-Mello, Diogo C. [UNESP] (Springer Nature, 2013)
Background: The accumulation of repetitive DNA during sex chromosome differentiation is a common feature of many eukaryotes and becomes more evident after recombination has been restricted or abolished. The accumulated repetitive sequences include multigene families, microsatellites, satellite DNAs and mobile elements, all of which are important for the structural remodeling of heterochromatin. In grasshoppers, derived sex chromosome systems, such as neo-XY♂/XX♀ and neo-X1X2Y♂/X 1X1X2X2♀, are frequently observed in the Melanoplinae subfamily. However, no studies concerning the evolution of sex chromosomes in Melanoplinae have addressed the role of the repetitive DNA sequences. To further investigate the evolution of sex chromosomes in grasshoppers, we used classical cytogenetic and FISH analyses to examine the repetitive DNA sequences in six phylogenetically related Melanoplinae species with X0♂/XX♀, neo-XY♂/XX♀ and neo-X1X2Y♂/X1X1X 2X2♀ sex chromosome systems. Results: Our data indicate a non-spreading of heterochromatic blocks and pool of repetitive DNAs (C 0 t-1 DNA) in the sex chromosomes; however, the spreading of multigene families among the neo-sex chromosomes of Eurotettix and Dichromatos was remarkable, particularly for 5S rDNA. In autosomes, FISH mapping of multigene families revealed distinct patterns of chromosomal organization at the intra- and intergenomic levels. Conclusions: These results suggest a common origin and subsequent differential accumulation of repetitive DNAs in the sex chromosomes of Dichromatos and an independent origin of the sex chromosomes of the neo-XY and neo-X1X2Y systems. Our data indicate a possible role for repetitive DNAs in the diversification of sex chromosome systems in grasshoppers. © 2013Palacios-Gimenez et al.; licensee BioMed Central Ltd.
Keywords: chromosome; cytogenetics; data acquisition; DNA; evolutionary biology; gene expression; grasshopper; phylogenetics; tracking; Caelifera; Eukaryota; Melanoplinae